2003
DOI: 10.1161/01.cir.0000058743.15215.03
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Ischemia Promotes Atrial Fibrillation in Dogs

Abstract: Background-Coronary artery disease is a significant risk factor for atrial fibrillation (AF), but the basis for this association is incompletely understood. The present study evaluated the hypothesis that atrial ischemia can create a substrate for AF maintenance. Methods and Results-Atrial ischemia was induced by occlusion of an atrial arterial branch that did not provide blood flow to the ventricles. Atrial-arterial occlusion increased the duration of AF induced by burst pacing from 57Ϯ32 seconds (control) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
153
1
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(164 citation statements)
references
References 28 publications
4
153
1
6
Order By: Relevance
“…Sinno et al have demonstrated that atrial ischemia causes slow conduction in the ischemic zone, resulting in a substrate for AF maintenance. 21 Incomplete cryoablation near the valvular annulus or coronary sinus during the Maze procedure has been postulated to incisional macroreentry around the mitral or tricuspid valves. Shah et al described slow conduction through the isthmus created by incomplete ablation causing sustained stable AFL.…”
Section: Discussionmentioning
confidence: 99%
“…Sinno et al have demonstrated that atrial ischemia causes slow conduction in the ischemic zone, resulting in a substrate for AF maintenance. 21 Incomplete cryoablation near the valvular annulus or coronary sinus during the Maze procedure has been postulated to incisional macroreentry around the mitral or tricuspid valves. Shah et al described slow conduction through the isthmus created by incomplete ablation causing sustained stable AFL.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial ischemia induced by occlusion of the atrial artery has been shown to cause local conduction slowing, with re-entry contributing to increased AF [21]. The cardiovascular effects of myocardial ischemia in ventricular infarction and dysfunction, increased atrial stretch, pericarditis, and neurohormonal and autonomic nervous system changes are potentially important contributors to a heterogeneous electrical and structural milieu, thereby increasing the risk of AF [22][23][24][25][26][27].…”
Section: Influence Of Epa/dha On Af In Ihdmentioning
confidence: 99%
“…экспериментальная ишемия миокарда предсердий приводила к нарушению про-ведения и формирования импульса, возникновению волн re-entry и развитию ФП [46]. Alasady и соавт.…”
Section: New-onset Atrial Fibrillation In Acs впервые возникшая фибриunclassified